Can Contractionary Fiscal Policy be Expansionary? Evidence from Tunisia - Khanfir, Wissem (Asian Journal of Economic Modelling, 2017)
In this paper, we study the non-linear relationship between fiscal policy and private consumption in Tunisia from 1975 to 2010. Our analysis, which is based on a threshold regression (TR) model proposed by Hansen (2000) confirms the non-linearity of the relationship between fiscal policy and private consumption, indicating an estimated threshold of public debt equal to 57% of GDP. The empirical results indicate that when public debt exceeds 57% of GDP, tax revenues are positively associated with private consumption. This finding confirms the expansionary fiscal contraction (EFC) hypothesis, occurring via tax revenues increases.